Nanocomposites for Environmental and Energy Applications - Ismail, Ahmad Fauzi; Goh, Pei Sean (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Environmental and energy issues are the two major problems that our world is facing today. The establishment of sustainable and innovative solutions are needed to address emerging problems. Functional nanocomposites are emerging materials that have become important due to their astonishing chemical and physical properties. The synergy effects rendered by a wide spectrum of nanomaterials and host materials have shown unlimited potential and advantages in many practical applications. Specifically, various nanocomposites are known to serve as sustainable solutions to curb global issues that are related to environmental pollution and energy shortage. This Special Issue of Nanomaterials, "Nanocomposites for Environmental and Energy Applications", aims at collecting a compilation of articles, which cover research articles, reviews, and communications, with topic areas focused on the development of the state-of-the-art nanocomposites to tackle environment and energy-related issues.